Serum Biochemistry and Serum Cortisol Levels of Immobilized and Hunted Muskoxen (Ovibos moschatus) from Northern Canada - Harms, N. Jane; Elkin, Brett T.; Gunn, Anne; Tracz, Boyan; Adamczewski, Jan; Flood, Peter; Leighton, Frederick A. (ARCTIC, 2012)
Muskoxen (Ovibos moschatus) are Arctic-adapted ruminants native to the Arctic regions of Canada, Alaska, and Greenland. Little is known about the serum biochemistry and serum cortisol of this species, or the effects of chemical immobilization on serum biochemical parameters. This study aimed to describe blood chemistry parameters and cortisol levels in hunted, tame, and chemically immobilized muskoxen and to examine differences in blood chemistry parameters and levels of stress associated with different capture techniques. Serum was collected from 91 adult female muskoxen in northern Canada. For analysis, these muskoxen were classified into six groups, five of free-ranging muskoxen (10 animals shot from snowmobiles near Kugluktuk, Nunavut; 18 chemically immobilized from a helicopter near Kugluktuk; 8 chemically immobilized from a helicopter near Norman Wells, Northwest Territories; 17 shot from snowmobiles near Cambridge Bay, Nunavut; 33 chemically immobilized from a snowmobile near Kugluktuk) and one of tame muskoxen (five tame animals maintained on pasture near Saskatoon, Saskatchewan). All samples were analyzed for cortisol, and 26 serum biochemistry parameters were measured in serum collected from three of the six groups (n = 36). Comparison of four groups showed that serum cortisol levels of muskoxen chemically immobilized from a helicopter near Kugluktuk were significantly higher(p < 0.05) than those of muskoxen chemically immobilized from snowmobiles or shot. A comparison of serum biochemistry from the groups of muskoxen shot and immobilized near Kugluktuk found that serum sodium, creatinine, phosphorus, magnesium, and creatine kinase were significantly higher (p < 0.05) in hunted muskoxen than in chemically immobilized animals, while urea, glucose and gamma glutamyl transferase were significantly higher (p < 0.05) in immobilized muskoxen. Most serum biochemical parameters, however, were similar to those of captive muskoxen. This evidence of differences between hunted and immobilized muskoxen in ...